2020
DOI: 10.1371/journal.pone.0233945
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of Listeria monocytogenes during co-cultivation with cheese rind bacteria suggests adaptation by induction of ethanolamine and 1,2-propanediol catabolism pathway genes

Abstract: The survival of Listeria (L.) monocytogenes in foods and food production environments (FPE) is dependent on several genes that increase tolerance to stressors; this includes competing with intrinsic bacteria. We aimed to uncover genes that are differentially expressed (DE) in L. monocytogenes sequence type (ST) 121 strain 6179 when co-cultured with cheese rind bacteria. L. monocytogenes was cultivated in broth or on plates with either a Psychrobacter or Brevibacterium isolate from cheese rinds. RNA was extract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 101 publications
(236 reference statements)
3
25
0
Order By: Relevance
“…We also observed that Rli47 was by far the most expressed gene during co-cultivation, further linking the functions of Rli47 and the CDGC (Anast and Schmitz-Esser, 2020). The authors of some recent studies (Tang et al, 2015;Tirumalai, 2015;Anast and Schmitz-Esser, 2020) concur that L. monocytogenes is most likely searching for alternative nutrients to fit into competitive niches, perhaps in a more cooperative approach.…”
Section: Implications For Survival In Food and Food Production Envirosupporting
confidence: 71%
See 4 more Smart Citations
“…We also observed that Rli47 was by far the most expressed gene during co-cultivation, further linking the functions of Rli47 and the CDGC (Anast and Schmitz-Esser, 2020). The authors of some recent studies (Tang et al, 2015;Tirumalai, 2015;Anast and Schmitz-Esser, 2020) concur that L. monocytogenes is most likely searching for alternative nutrients to fit into competitive niches, perhaps in a more cooperative approach.…”
Section: Implications For Survival In Food and Food Production Envirosupporting
confidence: 71%
“…L. monocytogenes also increased expression of the pdu gene cluster in co-culture biofilm with Bacillus subtilis but not in mono-culture biofilm (Tirumalai, 2015). Recently, a study from our laboratory that co-cultured L. monocytogenes with either a Brevibacterium or Psychrobacter food isolate found that the CDGC was highly upregulated in a modular way and was dependent on co-culture condition (Anast and Schmitz-Esser, 2020). We also observed that Rli47 was by far the most expressed gene during co-cultivation, further linking the functions of Rli47 and the CDGC (Anast and Schmitz-Esser, 2020).…”
Section: Implications For Survival In Food and Food Production Enviromentioning
confidence: 99%
See 3 more Smart Citations